Relationship of Vitamin D Deficiency with Non-Motor Functions of Parkinson’s disease - Khan, Mohammad Sakhawat Hossen; Mouri, Umme Kulsum; Islam, Md Rashedul; Rahman, Tanbin; Rahman, Aminur; Ahmed, Jamal Uddin (Bangladesh Journal of Medicine, 2024)
Background: Parkinson’s disease (PD), a neurodegenerative disorder is associated with substantial public health and economic burdens. Low levels of vitamin D are a common finding in patients of PD. This study was conducted to assess the serum vitamin D level in PD patients and to investigate the relationship of the vitamin D level with non motor functions of Parkinson’s disease. Methods: This case-control study was conducted in Department of Neurology, BIRDEM General Hospital, Dhaka for a period of 12 months. A total of 120 participants, 60 patients with PD and 60 age and sex matched sample of healthy controls were enrolled and informed written consent was taken. Information on socio-demographic characteristics, clinical features, laboratory parameters and neurological examinations were assessed. A semi-structured questionnaire was used for data collection and data was analyzed with Statistical Package for Social Science (SPSS) version 24.0. Results: Age and gender was not significantly different between PD cases and controls. Mean vitamin D level was significantly lower among the patients with PD compared to controls (25.97±3.44 ng/ml vs38.47±5.08 ng/ml, (p<0.01). Among all the cases of PD, 45% had akathisia, 36.7% had depression and 40% had insomnia. According to Modified Hoehn and Yahr score 53.3% patients were in stage 1-2, 26.7% in stage 2-3 and 20% in stage >3.The mean vitamin-D level was 28.43±2.43, 24.06±1.57 and 21.92±1.62 in stage 1-2, stage 2.5-3 and stage>3 respectively and vitamin D level decreased significantly with advancement in stages of PD(p<0.01). While assessing the depression in patients with PD, it was observed that stages of PD was significantly associated with severity of depression, patients with >3 stage of PD was moderately severe (16.7%) and severely depressed (16.7%) than patients with <3 stage PD (p=0.009). Conclusion: Importance should also be given for recognition of non- motor symptoms in PD patients, since these symptoms have an impact on patient’s quality of life. Bangladesh J Medicine 2024; 35: 82-87